1998
DOI: 10.1038/bjc.1998.369
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of tumorigenic and metastatic potentials of human melanoma cell lines by mutated (143 Val-Ala) p53

Abstract: Summary Metastatic melanoma, compared with other cancers, appears to be unusual because of its low frequency of p53 mutations and prevalence of wild-type p53 protein in advanced malignancy. Here, we examined the effects of wild-type and mutated p53 (143 Val-Ala) on tumorigenic and metastatic potential of two human melanoma cell lines. The cell line UISO-MEL-4 contains wild-type p53 and is tumorigenic, whereas UISO-MEL-6 lacks p53 and produces lung and liver metastasis upon s.c. injection into athymic mice. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

1999
1999
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
(27 reference statements)
0
4
0
3
Order By: Relevance
“…The first aim of the study was to evaluate the relative toxicity of the three MLs towards six different human melanoma cell lines, two established from a primary melanoma (Rauth et al, 1998) and four established from melanoma lymph node metastases (Fodstad et al, 1988a(Fodstad et al, , 1988bEdward, 2001;Carey et al, 1976). All three MLs inhibited cell proliferation of the six cell lines in a dose dependent manner, however, distinct differences between the cytotoxicity of the three lectins were noted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first aim of the study was to evaluate the relative toxicity of the three MLs towards six different human melanoma cell lines, two established from a primary melanoma (Rauth et al, 1998) and four established from melanoma lymph node metastases (Fodstad et al, 1988a(Fodstad et al, , 1988bEdward, 2001;Carey et al, 1976). All three MLs inhibited cell proliferation of the six cell lines in a dose dependent manner, however, distinct differences between the cytotoxicity of the three lectins were noted.…”
Section: Discussionmentioning
confidence: 99%
“…The human melanoma cell lines UISO-Mel6 (established from a primary malignant melanoma, Rauth et al, 1998), MV3 (established from a metastatic melanoma lymph node, Edward, 2001), and MeWo (established from a metastatic melanoma lymph node of a white, 78-year-old male, Carey et al, 1976) were kindly provided from the Klinik für Dermatologie, Universitätsklinikum Hamburg-Eppendorf, Germany. The human melanoma cell lines Lox and FemX-1, both established from a metastatic lymph node, (Fodstad et al, 1988a(Fodstad et al, , 1988b were kindly provided by Dr. O. Fodstad (Department of Tumour Biology University of Oslo, Norway).…”
Section: Cell Linesmentioning
confidence: 99%
“…The effects of mutation or loss of p53 have been elucidated in numerous studies. Rauth and co‐workers suggested that mutated ( 143 Val‐Ala ) p53 , which retains DNA binding and some of the transactivation functions of the wild‐type (wt) p53 protein, suppresses tumorigenic and metastatic potentials of human melanoma cell lines in vivo [19]. Furthermore, despite the presence of SV‐40 T‐antigen, p53 levels influence the characteristics of the late stages of mammary tumor growth and accelerate metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…The human melanoma cell lines UISO-Mel6 (established from a primary malignant melanoma; see Rauth et al (1998)), MV3 (established from a metastatic melanoma lymph node; see Edward (2001)) and MeWo (established from a metastatic melanoma lymph node of a white, 78-year-old male; see Carey et al (1976)) were kindly provided by the Klinik für Dermatologie, Universitätsklinikum Hamburg-Eppendorf, Germany. The human melanoma cell lines LOX and FEMX-1 were both established from a metastatic lymph node (Fodstad et al, 1988a, b).…”
Section: Cell Linesmentioning
confidence: 99%